REPRESENTASI KEKUASAAN PEREMPUAN DALAM FILM THE INCREDIBLES 2 - Rafif Sujatmoko, Muhammad; Widagdo, M.Bayu (Interaksi Online, 2019)
Film as a media is one of the medium to understand about power ideology in gender through woman and man representation. Character building in action Hollywood film usually depict woman as complement and decoration for the male lead character. This research’s aim was to know about the standpoint used for representing woman power in a film that uses a female lead character. This research was a descriptive-qualitative research with Critical Discourse Analysis by Sara Mills. First, character analysis was conducted to unearth the depiction of female character through apeareance and role. Second, fragmentation analysis was conducted in which female body was reduced to certain fragments to see how female was represented in film media. Third, focalization analysis to determine the posision of female character from dialog aspect. Fourth, schemata analysis to show the power ideology of female character. The outcome from this research showed that female power was represented through a female lead character using a male standpoint. Based on the appeareance and personality, the female lead character used the element of power that can be associated with male characteristics and traits such as dominance, brave, asertive, and resistance that were far from femininity. The fragmentation of masculine female was represented through her leg and chest as signs of physical power and bravery. In the other side, the character was also represented through the face, back, hips, and buttocks as signs of sexual appeal. The standpoint of power was shown through the dominance with other characters which was narrated with masculine traits stylistic. To sum up, There was a connection found in schemata analysis that shown there was influence of male standpoint in representation of female power in the film.